Waiting for answer This question has not been answered yet. You can hire a professional tutor to get the answer.
How do you balance redox reactions in basic solution?
WARNING — this is a long answer. In basic solution, you balance redox equations as if they were in acid. At the end, you use OH⁻ to convert to base.
Balance the following equation in basic solution: MnO₄⁻ + CN⁻ → MnO₂ + CNO⁻
Step 1: Separate the equation into two half-reactions. MnO₄⁻ → MnO₂ CN⁻ → CNO⁻
Step 2: Balance all atoms other than H and O. Done
Step 3: Balance O by adding H₂O to the deficient side. MnO₄⁻ → MnO₂+ 2H₂O CN⁻+ H₂O → CNO⁻
Step 4: Balance H by adding H⁺ to the deficient side. MnO₄⁻+ 4H⁺ → MnO₂+ 2H₂O CN⁻+ H₂O → CNO⁻ + 2H⁺
Step 5: Balance charge by adding electrons to the more positive side. MnO₄⁻+ 4H⁺ + 3e⁻ → MnO₂+ 2H₂O CN⁻+ H₂O → CNO⁻ + 2H⁺ + 2e⁻
Step 6: Multiply each half-reaction by a factor that gives the lowest common multiple of the electrons transferred. In this case, the lowest common multiple of 3 and 2 is 6. We multiply the first half-reaction by 2 and the second half-reaction by 3.
2 × [MnO₄⁻+ 4H⁺ + 3e⁻ → MnO₂+ 2H₂O] 3 × [CN⁻+ H₂O → CNO⁻ + 2H⁺ + 2e⁻]
Step 7: Add the two half-reactions, cancelling any like terms.
2MnO₄⁻+ 3CN⁻+ 2H⁺ → 2MnO₂ + 3CNO⁻ + H₂O
This is the balanced equation in acid solution. We must now convert to base solution.
Step 8: Add enough multiples of the equations H⁺ + OH⁻ → H₂O or H₂O → H⁺ + OH⁻ to cancel the H⁺ in the redox equation, cancelling like terms.
2MnO₄⁻+ 3CN⁻+ 2H⁺ → 2MnO₂ + 3CNO⁻ + H₂O 2H₂O → 2H⁺ + 2OH⁻
2MnO₄⁻+ 3CN⁻+ H₂O → 2MnO₂ + 3CNO⁻ + 2OH⁻
Step 9: Check that atoms balance. On the left: 2 Mn; 9 O; 3 C; 3 N; 2 H On the right: 2 Mn; 9 O; 3 C; 3 N; 2 H
Step 10: Check that charges balance. On the left: 2- + 3- = 5- On the right: 3- + 2- = 5-
The balanced equation is 2MnO₄⁻+ 3CN⁻+ H₂O → 2MnO₂ + 3CNO⁻ + 2OH⁻